Impact of Structural Adjustment Programme (SAP) on Nigerian agriculture and rural life : volume III: Benue, Cross River and Imo States - CBN/NISER (Ibadan, Nigeria : CBN/NISER, 1992)
This report was part of the conference proceeding on SAP held in Ibadan to generate needed data which will further reveal the real situation in agriculture and rural life in Nigeria since SAP, as a guide to policy makers and the general public
Vol III: Benue, Cross River and Imo States.
Includes bibliographical references.
osa 10/05/2018
Loans
Keywords: Agricultural Development; Economic Situation; Nigeria